2013
DOI: 10.1002/micr.22067
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of composite defect of bone and soft tissues with a combined latissimus dorsi and serratus anterior and RIB free flap

Abstract: LD-SA/rib free flap should be regarded as an effective procedure for reconstruction of composite tissue defects in patients who are not candidates for more commonly used vascularized bone-containing free flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 38 publications
0
42
0
3
Order By: Relevance
“…The combined use of the latissimus dorsi and serratus anterior flap has been reported for larger defects. [9][10][11] It is possible to transfer vascularized ribs with serratus anterior muscle as a composite flap, which is a useful option in the simultaneous reconstruction of soft tissue and cranium. [11] The rectus abdominis muscle or musculocutaneous flap can be used in medium-sized scalp defects.…”
Section: Introductionmentioning
confidence: 99%
“…The combined use of the latissimus dorsi and serratus anterior flap has been reported for larger defects. [9][10][11] It is possible to transfer vascularized ribs with serratus anterior muscle as a composite flap, which is a useful option in the simultaneous reconstruction of soft tissue and cranium. [11] The rectus abdominis muscle or musculocutaneous flap can be used in medium-sized scalp defects.…”
Section: Introductionmentioning
confidence: 99%
“…Five publications were identified that treated a total of 22 patients with a thoracodorsal based composite flap with vascularized rib for infected cranioplasty, osteomyelitis, and brain tumor. A 100% union rate was achieved in all cases but the average time for bone union was not specified in any studies.…”
Section: Resultsmentioning
confidence: 99%
“…We retrospectively reviewed the charts of 47 patients, who had 48 combined bone and soft tissue defects, treated by the senior author (HCC) with one stage, composite, vascularized bone and soft tissue transfer procedure with a thoracodorsal based composite flap with vascularized rib either pedicled or free at Chang Gung Memorial Hospital (Taipei) and China Medical University Hospital (Taichung) between 1983 and 2017. Twelve of these cases made the subject of material previously published . Patients data are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, another study reported the use of the serratus anterior muscle flap but in combination with a latissimus dorsi flap in a case of massive malignant endothelioma involving the scalp with positive outcomes [16]. Trignano and colleagues also reported the usefulness of a combined latissimus dorsi/serratus anterior flap with superadded rib free flap as an alternative procedure of vascularized coverage of composite tissue defects following variable lesions involving scalp or extrimities [17]. Taniguchi and colleagues used a latissimus dorsi myocutaneous flap alone as skin coverage for a scalp defect following repeated surgical excisions of recurrent DFSP but with subsequent administration of Urokinase (which was not used in our case) [6].…”
Section: Discussionmentioning
confidence: 99%